Unexplained enhancements of CH3Br in the Arctic and sub-Arctic lower troposphere during TOPSE spring 2000 - Wingenter, OW; Sive, BC; Blake, DR; Rowland, FS; Ridley, BA (eScholarship, University of California, 2003)
Elevated concentrations of methyl bromide (CH3Br) were observed in the Arctic atmospheric boundary layer (BL) during periods of widespread BL ozone (O3) depletion episodes (ODEs: O3 mixing ratios < 20 × 10-9 or parts per billion by volume, ppbv) particularly during major ODEs (MODES: O3 < 4 ppbv). No other organic gases measured during TOPSE (Tropospheric Ozone Production about the Spring Equinox) exhibited anti-correlations with O3 during these ODEs. Methyl bromide has both natural and anthropogenic sources and contributes ∼ half of the bromine (Br) to the stratosphere, where it can catalytically destroy O3. Several known CH3Br sources are evaluated, but the current knowledge cannot explain the observed enhancements. If the mechanism is direct gasphase photochemical production, a significant portion of the unknown CH3Br source may be found.